Slovensko gorica/zorica 'dvorišče', '(vaški) trg', 'ograda' - Šivic-Dular, Alenka (Slavistična revija, 1996)
The accessible material for Sln. word gorica/zorica 'front yard', '(village) square', 'enclousure' and the previous etymological explanations based on a word-formational-semantic analysis enable us to posit a new etymological explanation ot the word from *dvorica (from Csl. * dvor´).
Keywords: dialect; dialectology; dialektologija; etimologija; etymology; leksikologija; lexicology; narečja; Slovene; slovenščina